INDEKS INKLUSI KEUANGAN INDONESIA (ANALISIS KONTRIBUSI SEKTOR USAHA LEMBAGA KEUANGAN MIKRO) - h holle, Mohammad (DE'RECHTSSTAAT, 2022)
Financial inclusion aims to provide the general public with access to a variety of financial services and products that are suited to the community's abilities and requirements, particularly for those who are unbanked. The goal of this study is to identify and examine Indonesia's financial inclusion index from the perspective of the microfinance institution business sector, as well as the obstacles, opportunities, and challenges that policymakers face in increasing the financial inclusion index, which has implications for improving people's welfare. The Indonesian financial inclusion index from the microfinance institution business sector, as well as other business sectors, were compared using the research method of literature study. The descriptive qualitative technique employs an inductive process as an analytical tool. Based on the research results, 1. Indonesia's financial inclusion index is still quite low, contributed by the microfinance institutions (MFI) sector. Community groups in Indonesia have not fully utilized official financial services, especially as the main source of cash and financing. As a result, policymakers must expand the availability of financial inclusion. In 2019, Indonesia's financial inclusion index was 76.19 percent. increase from the previous year. The banking industry contributed the most (73.88%), followed by financial institutions (14.56%), insurance (13.15%), pawnshops (12.38%), pension funds (6.18%), and the capital market (1.55%). The MFI business sector, on the other hand, contributes only 0.72 percent.This demonstrates that the MFI, which is the foundation of the community's economy, contributes the least. 2. Financial literacy accounts for only 0.85% of Indonesia's financial inclusion index, posing a challenge to efforts to increase the country's financial inclusion index. MFIs are anticipated to strengthen the economy of the community, but because they provide small-scale funding, it is critical to increase their participation. Microfinance, on the other hand, provides micro-entrepreneurs, low-income organizations, and needy households with loans, deposits, money transfers, insurance, and payments.